(3cJGH GdMLQ GdCShOs - (3eLghds ((3eUWai Hf eMeOs)
(3ChdgG (B:s
(3HSe Gddg GdHGH GdMLQ GdCShO GdPj dG GHJOGA hdG GfJgGA dg JCNP efg (B((3WQHG(B) (3gj jhe ef jhegG CjGe GdQHjY GdHGdZjf aJZSdg ZSdG s
(3BNQgG (B:s
(3hbGd HYVge Ef de jcf YfOc ef GdeGA GdEdgj aNP ef GdeGFjf GdeeRhLjf HGdcdS GdOGNd aj GdJQcjH GdChd hCda efg Ydi GdEcSjQ Ydi Pdc GdMSGH hGdYed hGMO hGdMeO ddg Jes
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdcjejGA hGdWHjYjGJs